2021
DOI: 10.1021/acsearthspacechem.1c00177
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Calcium Carbonate Polymorphs by Cerussite

Abstract: Calcium carbonate (CaCO3) polymorphs, calcite, aragonite, and vaterite, serve as a major sink to retain various metal ions in natural and engineered systems. Here, we visualize the systematic trends in reactivities of calcite, vaterite, and aragonite to Pb2+ dissolved in acidic aqueous solutions using in situ optical microscopy combined with ex situ scanning electron and transmission X-ray microscopies. All three polymorphs undergo pseudomorphic replacement by cerussite (PbCO3) but with distinct differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…31−33 A recent study by Kim et al provided insight into this conversion process for all three polymorphs of CaCO 3 and found that the mechanism is one of interface-mediated dissolution/recrystallization in acidic solution. 34 All three polymorphs showed the capacity to undergo the conversion but with different efficacies dictated by solubility constant, dissolution rate, crystal habit, and surface areas of the initial microstructures. Vaterite and aragonite, growing in polycrystalline aggregates, possess a higher surface area than euhedral single-crystal microstructures of calcite, causing faster dissolution on exposure to an acidic solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31−33 A recent study by Kim et al provided insight into this conversion process for all three polymorphs of CaCO 3 and found that the mechanism is one of interface-mediated dissolution/recrystallization in acidic solution. 34 All three polymorphs showed the capacity to undergo the conversion but with different efficacies dictated by solubility constant, dissolution rate, crystal habit, and surface areas of the initial microstructures. Vaterite and aragonite, growing in polycrystalline aggregates, possess a higher surface area than euhedral single-crystal microstructures of calcite, causing faster dissolution on exposure to an acidic solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This causes the resulting PbCO 3 formed over the initial CaCO 3 microstructure to precipitate in much the same morphology as the layer beneath, effectively allowing for the retention of crystal morphology, though causing the change in surface texture and an apparent reduction in transparency (Figure 1B,E). 34 It is anticipated that this type of cerussite shell may be porous, allowing Pb 2+ ions in solution to migrate to the CaCO 3 /PbCO 3 interface to continue the process of conversion to PbCO 3 . 31,35 The pH of the Pb(NO 3 ) 2 conversion solution in the present work was measured and was found to be acidic with an average initial pH of 3.92; hence, we propose that the conversion process proceeds by the same mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molar volume increases involved in the calcite-by-strontianite (Δ V = + 2.07 cm 3 /mol; +5.6%) and calcite-by-witherite (+8.87 cm 3 /mol; +24.1%) replacement reactions determine the formation of very compact overgrowths which only contain a small volume of isolated micropores. The lack of interconnected porosity within these overgrowths makes them impermeable to the fluid, preventing significant mass transfer from the bulk fluid to the reactive interface between the Volmer–Weber replacement layer and the unaltered calcite core. , Slight differences in the molar volume change involved in both replacement reactions can result from differences in the amount of Ca incorporated into strontianite and witherite as this incorporation will contribute to the decrease of the molar volume of both phases. In any case, the impact of these differences on the textural features of the strontianite- and witherite-replaced layers will be very small and will not significantly affect the effectiveness of their armoring of the calcite surface.…”
Section: Discussionmentioning
confidence: 99%
“…XMT has also revealed the complex interplay during dissolution/precipitation coupled reactions or phase transformation, which are explored using either single crystals [Kim et al, 2021] or aggregates confined in pressure vessel. For example, Fusseis et al [2012] and Bedford et al [2017] have provided insights in the dehydration reactions during heating of gypsum (CaSO 4 , 2H 2 O) and subsequent transformation into bassanite (CaSO 4 , 0.5H 2 O), whereas Zheng et al [2017] have investigated the hydration of periclase (MgO) into brucite (Mg(OH) 2 ).…”
Section: Mineral Reactivitymentioning
confidence: 99%